System productivity enhancement in coconut (Cocos nucifera) garden by intercropping with flower crops in Assam - NATH, J C; DEKA, K K; MAHESWARAPPA, H P; SUMITA, S (The Indian Journal of Agricultural Sciences, 2019)
The field experiment was conducted at Horticultural Research Station, Kahikuchi of Assam Agricultural University for four consecutive years (2012–13 to 2015–16) to study the performance of flower crops as intercrop in adult coconut (Cocos nucifera) garden spaced at 7.5 m × 7.5 m taking five commercial flower crops, viz. Tuberose (Polianthes tuberosa) var. Single, Gerbera (Gerbera jamesonii) var. Red Monarch, Bird of Paradise (Strelitzia reginae) var. Glauca, Gladiolus (Gladiolus grandiflorus) var. Oscar, Marigold (Tagetes erecta) var. Siracole along with a control (coconut monocrop). Results showed that number of leaves on the crown, annual leaf production, number of inflorescences per palm and nut yield of coconut was not significantly influenced by the flower crops grown in coconut garden. Significantly the highest total coconut equivalent yield of 48920 nuts/ha/year was obtained in coconut + gerbera followed by coconut + tuberose (42717 nuts/ha/year), coconut + gladiolus (42334 nuts/ha/year) and the lowest in coconut as monocrop (10430 nuts/ha/year). Intercropping system of growing gerbera in coconut garden registered the highest net income (` 380075/ha) and B:C ratio (3.5) followed by tuberose (` 323420/ha and 3.1), gladiolus (` 315090/ha and 2.9), marigold (` 233050/ha and 2.8) and the lowest net income of ` 64050/ha and B:C ratio (1.6) obtained in monocropping of coconut.